2015
DOI: 10.1039/c4cc08529a
|View full text |Cite
|
Sign up to set email alerts
|

Copper–palladium core–shell as an anode in a multi-fuel membraneless nanofluidic fuel cell: toward a new era of small energy conversion devices

Abstract: A membraneless nanofluidic fuel cell with flow-through electrodes that works with several fuels (individually or mixed): methanol, ethanol, glycerol and ethylene-glycol in alkaline media is presented. For this application, an efficient Cu@Pd electrocatalyst was synthesized and tested, resulting outstanding performance until now reported, opening the possibility of power nano-devices for multi-uses purposes, regardless of fuel re-charge employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…These shifts on the diffraction peaks of Cu@Pd and Cu@Pt indicated that there is a solid solution but not a segregation of the noble metal on the surface, being confirmed by TEM. The XRD patterns for the commercial Pd/C electrocatalyst exhibited peaks located at 2h = 40.3, 46.78, 68.22, 82.12, and 86.94°, which are characteristic of a face-centered cubic structure for Pd and correspond to their (1 1 1), (2 0 0), (2 2 0), (3 1 1), and (2 2 2) planes, respectively [22,29,30]. Furthermore, the XRD pattern for the Cu@Pd/C electrocatalyst shows a shifting toward higher 2h values as the Cu@Pt/C electrocatalysts, their values were 2h = 41.41, 48.30, 70.95, and 85.85°, which correspond to its (1 1 1), (2 0 0), (2 2 0), and (3 1 1) planes, respectively [22].…”
Section: Physicochemical Characterization Of Cu@pd/c and Cu@pt C Elecmentioning
confidence: 98%
See 3 more Smart Citations
“…These shifts on the diffraction peaks of Cu@Pd and Cu@Pt indicated that there is a solid solution but not a segregation of the noble metal on the surface, being confirmed by TEM. The XRD patterns for the commercial Pd/C electrocatalyst exhibited peaks located at 2h = 40.3, 46.78, 68.22, 82.12, and 86.94°, which are characteristic of a face-centered cubic structure for Pd and correspond to their (1 1 1), (2 0 0), (2 2 0), (3 1 1), and (2 2 2) planes, respectively [22,29,30]. Furthermore, the XRD pattern for the Cu@Pd/C electrocatalyst shows a shifting toward higher 2h values as the Cu@Pt/C electrocatalysts, their values were 2h = 41.41, 48.30, 70.95, and 85.85°, which correspond to its (1 1 1), (2 0 0), (2 2 0), and (3 1 1) planes, respectively [22].…”
Section: Physicochemical Characterization Of Cu@pd/c and Cu@pt C Elecmentioning
confidence: 98%
“…This design was based on a previous report [22,23]. Carbon nanofoam (Marketech International, Inc.) was used as the basis for the threedimensional flow-through electrodes tested in this study.…”
Section: Air-breathing Nanofluidic Fuel Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the fuel cells category, different organic liquid fuels were used as benign fuel, such as methanol, formic acid, ethanol or ethylene glycol. [12][13][14][15] For example, Esquivel et al presented a paper-based direct methanol fuel cell that can be integrated within lateral flow test strips. 15 However, the electrochemical reactions involving these organic liquid fuels often require precious metal catalysts such as platinum or palladium that are scarce and thus not readily disposable.…”
mentioning
confidence: 99%